Liver Transplantation Selection and Allocation Criteria for Hepatocellular Carcinoma: A European Perspective - Moeckli, Beat; Majno, Pietro; Orci, Lorenzo A.; Peloso, Andrea; Toso, Christian (Seminars in Liver Disease, 2021)
For patients with early-stage hepatocellular carcinoma (HCC), liver transplantation offers the best chance of cure. Over the past two decades, selection criteria to determine eligibility for liver transplantation have been constantly refined but a fair allocation strategy of liver grafts to HCC patients remains challenging. In Europe, over a dozen transplantation networks apply different liver transplantation criteria for HCC patients. In this review, we explore and compare candidate selection and liver graft allocation strategies for patients with HCC with a European perspective and discuss the ethical and technical challenges involved. In addition, we suggest possible paths for future improvement such as transitioning from fixed selection and allocation criteria to a more flexible model of benefit, which includes criteria concerning the graft, response to treatment, the biology of the tumor, and other relevant recipient factors.
Keywords: liver transplantation; HCC; allocation; transplant benefit; selection